SITTING MEDITATION TRAINING AS AN ALTERNATIVE TO SELF-HEALING - Sastri, Prinska Damara; Nuraeni, Yashinta Audina; Ardiansyah, Rizal; Nurfadilah, Nurfadilah; Suwandi, Zulfiani Rahmatika (Inaba of Community Services Journal, 2022)
The prevalence of mental disorders in Indonesia shows that many cases of mental disorders such as anxiety, depression and suicidal ideation that occur in Indonesia, one of which occurs in the productive age. One of the efforts that can be done is to provide the community with self-healing, one of which is by introducing the sitting meditation method to the community. Mental health disorders can occur due to negative thoughts and emotions that trigger cycles of thoughts and feelings. The sitting meditation method is believed to aim to increase sensitivity to the present state, which consists of several activities such as concentration, and relaxation by balancing logical or rational thinking with empathy which tends to be feeling based and practicing mindfulness with an observative attitude. This sitting mediation method, if practiced regularly, will naturally produce a state of calm, clarity and happiness. This method of sitting meditation is given in the form of a webinar to the Ruang Ceurita Community which contains information and practical tips for implementing sitting meditation, with a duration of 1 hour. The question-and-answer session will conclude the webinar, followed by a questionnaire on the implementation of the webinar.